تطبيق قانون المنافسة على الصفقات العمومية - بين النصوص القانونية والإشكالات التطبيقية - - تياب, نادية; أحميد, هنية (University of Eloued جامعة الوادي, 2021)
نظرًا لأهمية المنافسة في مجال الصفقات العمومية أقر لها المشرع حمايةً خاصة كان ذلك بتكريسها في تنظيم الصفقات العمومية وإيجاد الضمانات القانونية الكفيلة بتجسيدها، إذّ أجاز تطبيق قانون المنافسة في مجالها وكل إخلال بأحكامها يفتح المجال لإمكانية تدخل مجلس المنافسة. فالتوجه اليوم يسير نحو إخضاع أعمال الإدارة وعلى جانب مهم من نشاطاتها الإدارية إلى قانون المنافسة وإنّ كان تطبيقه يتم بالكيفية التي لا تعيق أداء الشخص العمومي لمهام المرفق العام. غير أن ذلك أثار الكثير من الإشكالات العملية والتطبيقية أساسها غموض النص القانوني في هذا المجال وتداخل الاختصاص بين القضاء الإداري ومجلس المنافسة حال دون تحقيق الأهداف المرجوة. Considering the importance of competition in the field of public works contracts, the Legislator instituted for the same a particular protection by the consecration of competition in organizing public works contracts and finding the legal guarantees which guarantee its materialization. Since, the Legislator permitted the application of competition law in its field and any breach of its provisions leads to the possibility of the intervening of the Competition Council. Today’s trend is towards submitting administration works and an important side of its administrative activities to competition law which application is carried out in a way not to obstruct the public officer from performing public service missions. However, this raised many operational and practical issues due to the ambiguity of the legal text in this field and the interference of competence between Administrative Justice and the Competence Council which prevent from achieving the expected goals.
مجلد12، عدد1
Keywords: المنافسة ; الصفقات العمومية ; مجلس المنافسة ; قانون المنافسة ; المرفق العام ; المال العام; Competition; public transactions contracts; Competition Council; Copetition Law; public service, public funds